A New Operational Method for Solving Nonlinear Volterra Integro-differential Equations with Fractional Order - Moghadam, M. Mohseni; Saeedi, H.; Mollahasani, N. (Journal of Informatics and Mathematical Sciences, 2010)
In this paper we introduce a new operational method, which is based on the generalized Taylor formula and Caputo fractional derivative. We employ this method to solve a fractional Volterra integro-differential equation with supplementary conditions. Some examples are included to demonstrate the validity and applicability of the technique. Numerical results confirm the efficiency of the method.